Literary works as a means of promoting cultural heritage, on the example of Outlander - Juhászová, Rebeka (Revista Arheologică, 2026)
Cultural heritage plays a key role in shaping the collective identity of nations while also providing an important context for language and cultural education. This paper examines literary works as an effective means of promoting cultural heritage, with a focus on Outlander, written by Diana Gabaldon, as the primary text for further interpretation. The main goal of the paper is to demonstrate, through the lens of a historical approach, that cultural heritage is not a static phenomenon but a living and dynamic element actively used in the creation of contemporary literary works, and to show that literary texts incorporate and reinterpret elements of heritage, making them accessible and meaningful for contemporary audiences. At the same time, the paper highlights that literature enables readers to internalise historical and cultural contexts more effectively by embedding them within engaging storylines and emotionally resonant experiences. Methodologically, the article employs close reading, textual analysis, and thematic analysis. Based on interpretation, the paper discusses the broader potential of literature as a tool for promoting cultural heritage both within formal educational settings and beyond them, contributing not only to cultural awareness but also to the development of cultural tourism and regional growth.
Keywords: cultural heritage; Outlander; literature; educational tool; Celts; history